Acute effect of sodium bicarbonate supplementation on the performance during CrossFit® training - Luiz Paulo Toledo; João Guilherme Vieira; Marcelo Ricardo Dias (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To verify the acute effect of sodium bicarbonate (NaHCO3) supplementation on performance during CrossFit® workout. Methods: Nine experienced males (30.8 ± 3.5 years; 84.4 ± 9.5 kg; 177.5 ± 4.03 cm; 2.2 ± 1.0 years) in CrossFit® participated in this study. They were allocated to two conditions: a) supplementation with 0.3 g.kg-1 of body weight of NaHCO3 and b) supplementation with 0.045 g.kg-1 of body weight of sodium chloride (NaCl). Blood lactate was analyzed at two different moments: before (lac-pre) and after the training protocol (lac-post). The heart rate (HR) and the rating of perceived exertion (RPE) were also collected every two minutes during the execution of the training protocol, and the RPE was also collected after it was finished. At the end of the training protocol, a questionnaire to measure gastrointestinal side effects (GSE) was answered by the participants. Repetitions performed in the training protocol was computed to evaluate the performance during the workout. Results: The results showed that there were no differences found when comparing the conditions for all parameters. HR and RPE were different in the first few minutes (< 4-6 minutes) when compared to the final minutes (> 14 minutes) of the workout. The area under the curve of HR and RPE was significantly lower in the NaHCO3 condition. Conclusion: Acute NaHCO3 supplementation did not improve performance during workout 'Cindy' in experienced men. Supplementation also did not alter hemodynamic and perceptual parameters, nor did it cause any GSE. However, responses as a function of time were reduced with NaHCO3 supplementation.